2021
DOI: 10.1609/icwsm.v10i1.14757
|View full text |Cite
|
Sign up to set email alerts
|

“Blissfully Happy” or “Ready toFight”: Varying Interpretations of Emoji

Abstract: Emoji are commonly used in modern text communication. However, as graphics with nuanced details, emoji may be open to interpretation. Emoji also render differently on different viewing platforms (e.g., Apple’s iPhone vs. Google’s Nexus phone), potentially leading to communication errors. We explore whether emoji renderings or differences across platforms give rise to diverse interpretations of emoji. Through an online survey, we solicit people’s interpretations of a sample of the most popular emoji characters,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 7 publications
1
64
0
2
Order By: Relevance
“…Emojis: interpretation and meaning. Previous research has shown that emojis are often misunderstood (Miller et al 2016(Miller et al , 2017. Misunderstanding is sometimes related to how the emoji's design is interpreted in context or the way it is shown on the receiving side.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Emojis: interpretation and meaning. Previous research has shown that emojis are often misunderstood (Miller et al 2016(Miller et al , 2017. Misunderstanding is sometimes related to how the emoji's design is interpreted in context or the way it is shown on the receiving side.…”
Section: Related Workmentioning
confidence: 99%
“…Our work studies the intrinsic ability of emojis to convey information, independent of the textual context they are used in. In contrast to Miller et al (2016Miller et al ( , 2017, who focused on small subsets of anthropomorphic emojis, we consider a far more exhaustive set of emojis (see Table 1). The aspiration of an emoji-based language.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Users apply emojis to make a message more engaging to the recipient, or for relationship maintenance (Hu et al 2017). The differences in emoji usage are demonstrated across communities, such as, apps, platforms, languages, cultures and genders (Tauch and Kanjo 2016; Lu et al 2016;Chen et al 2018b;Barbieri et al 2016;Miller et al 2016). Besides the study of emoji usage in social media, researchers also develop models to incorporate emoji information in the downstream tasks.…”
Section: Emojismentioning
confidence: 99%
“…Hashtags usually consist of abbreviated or concatenated concepts, making them hard to understand for outside observers. Emojis have also been associated with great ambiguity due to the rich information coded in the tiny pictures (Miller et al 2016). On the other hand, although some previous work assumes a hidden correlation between emojis and hashtags (Park, Xu, and Fung 2018), little research has explicitly examined the relationship between hashtags and emojis.…”
Section: Introductionmentioning
confidence: 99%